2016
DOI: 10.1128/jvi.01772-15
|View full text |Cite
|
Sign up to set email alerts
|

Four Amino Acid Changes in HIV-2 Protease Confer Class-Wide Sensitivity to Protease Inhibitors

Abstract: Protease is essential for retroviral replication, and protease inhibitors (PI) are important for treating HIV infection. HIV-2 exhibits intrinsic resistance to most FDA-approved HIV-1 PI, retaining clinically useful susceptibility only to lopinavir, darunavir, and saquinavir. The mechanisms for this resistance are unclear; although HIV-1 and HIV-2 proteases share just 38 to 49% sequence identity, all critical structural features of proteases are conserved. Structural studies have implicated four amino acids in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…(1999) detected a structural asymmetry adjacent to the nucleotide-binding sites of aspartate transcarbamoylase that would appear to account for their separation into high- and low-affinity binding sites 33 . Despite their strong chemical similarity (Tanimoto coefficient = 0.95), DRV and APV exhibit completely different susceptibility against PR2 2 , 7 . By comparing the asymmetric profiles of PR2 dimers complexed with APV and DRV, we observed some differences that may be involved in the better recognition or higher affinity between DRV and PR2, particularly in the binding pockets at positions 23, 31, 46, and 75.…”
Section: Discussionmentioning
confidence: 99%
“…(1999) detected a structural asymmetry adjacent to the nucleotide-binding sites of aspartate transcarbamoylase that would appear to account for their separation into high- and low-affinity binding sites 33 . Despite their strong chemical similarity (Tanimoto coefficient = 0.95), DRV and APV exhibit completely different susceptibility against PR2 2 , 7 . By comparing the asymmetric profiles of PR2 dimers complexed with APV and DRV, we observed some differences that may be involved in the better recognition or higher affinity between DRV and PR2, particularly in the binding pockets at positions 23, 31, 46, and 75.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, these compounds remained in the preclinical or early clinical stage not leading to an approved medicine 18 and their effectiveness for the novel virus might suffer due differences in single amino acids. 19 Accordingly, the development of specific inhibitors for SARS-CoV-2 main protease remains an urgent necessity in the scientific community 10-12 which is reflected by the multiple projects focusing on this protein. For example, three studies investigating the repurposing of marketed drugs proposed several candidates for SARS-CoV-2 treatment.…”
Section: Introductionmentioning
confidence: 99%
“…(2016), who reported the opposite observation by incorporating four HIV-1-like mutations, I32V, V47I, L76M, and I82V, into a wild-type PR2. This PR2 mutant exhibited susceptibility to all PIs perfectly equivalent to PR1 3 . In this last study, the authors also showed that mutations in the binding site induced only small rearrangements, modifying the internal interactions between PR2 and DRV compared to the PR1-DRV complex.…”
Section: Introductionmentioning
confidence: 90%
“…Currently, nine FDA (Food and Drug Administration)-approved PIs are available for HIV-1 therapy, including saquinavir (SQV), ritonavir, indinavir, nelfinavir, amprenavir (APV), lopinavir (LPV), atazanavir, tipranavir, and darunavir (DRV). Only three of these are commonly recommended for the treatment of HIV-2 infection: SQV, LPV, and DRV 1 , 3 , 4 . Greater understanding of the structural mechanisms underlying HIV-2 resistance to PIs is important for the development of new efficacious anti-HIV-2 drugs.…”
Section: Introductionmentioning
confidence: 99%